2008
DOI: 10.1586/14737140.8.8.1339
|View full text |Cite
|
Sign up to set email alerts
|

Colon and rectal cancer after renal transplantation

Abstract: Increased cancer risk after renal transplantation is believed to be a consequence of continuous immunosuppression. However, the risk of colorectal cancer (CRC) after renal transplantation is controversial and has received limited study. Accumulating evidence suggests that colon and rectal cancers have different characteristics in the post-renal transplant patient (PRTP) and should be evaluated separately in transplant registries. This article reviews the current literature evaluating CRC diagnosed in PRTPs, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(108 reference statements)
0
3
1
Order By: Relevance
“…Additionally, the mean exposure to the immunosuppressive agent is a significant risk factor in transplant recipients. Although a recent study showed that CRC in the transplant recipient developed at an earlier age compared to the general population,9,11 our data showed that age at diagnosis of the transplant recipient was not different from that of the control group. We do not regard younger age as an important risk factor, but long-term exposure to immunosuppression.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Additionally, the mean exposure to the immunosuppressive agent is a significant risk factor in transplant recipients. Although a recent study showed that CRC in the transplant recipient developed at an earlier age compared to the general population,9,11 our data showed that age at diagnosis of the transplant recipient was not different from that of the control group. We do not regard younger age as an important risk factor, but long-term exposure to immunosuppression.…”
Section: Discussioncontrasting
confidence: 81%
“…Recent evidence indicates that transplantation patients appear to be at a higher risk for developing CRC 9. Villeneuve, et al11 described an incidence of CRC after renal transplantation, showing 1.49 times higher than the standard incidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 These approaches should start with the screening of donors for cancer, thereby minimizing the required dose of immunosuppressive drugs, 4 the consumption of prophylactic antiviral drugs, 11 and the avoidance of carcinogenic factors such as high sun exposure. 12 Several types of cancers present in renal transplant populations, including skin cancers, 10 posttransplant lymphoproliferative disorders (PTLD), multiple myeloma, 13 non-Hodgkin's lymphoma, 14 Kaposi's sarcoma, 15 colorectal cancer, 16 and renal cell carcinoma. 17 Reported cases of brain tumors in the posttransplantation setting include lymphomas, glioblastomas, and oligodendrogliomas.…”
Section: Discussionmentioning
confidence: 99%